Hubungan Dukungan Suami dan Sikap Ibu Hamil Trimester III Terhadap Kesiapan Menghadapi Persalinan di Masa Pandemi COVID-19 di Puskesmas Gerokgak I - Ketut Eka Larasati Wardana; Kadek Lila Damayanti; Desak Ketut Sugiartini (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2023)
Background: The current Covid-19 pandemic greatly affects the condition of pregnant women, especially when they are about to face childbirth. Attention and support from the closest people, especially husbands, are very helpful in overcoming the anxiety experienced by pregnant women in facing childbirth in the Covid-19 era. Purpose: of this study was to determine the relationship between husband support and the attitude of third trimester pregnant women towards readiness to face childbirth during the Covid 19 pandemic at the Gerokgak I Primary Health Care. Method: used is quantitative analysis with a cross sectional approach using primary data with a data collection instrument in the form of a questionnaire distributed to 134 respondents where the sampling technique used is the Non Probability Sampling technique with the purposive sampling method conducted from September to November 2021. at the Grokgak I Primary Health Care. Results: showed p value <0.05, which means ha is accepted and h0 is rejected. Conclusion: obtained is that there is a relationship between husband's support and the attitude of pregnant women in the third trimester of readiness to face childbirth during the COVID-19 pandemic. Suggestions It is necessary to provide health information or health education to husbands of pregnant women about pregnancy support and readiness to face childbirth during the COVID-19 pandemic. and the role of midwives or other health workers to improve Communication, Information and Education (KIE) on how to deal with pregnancy and childbirth in pregnant women during the Covid-19 pandemic.